Exploring ginhawa as an indigenous concept of well-being through the lens of folk healers, clients and community residents in Pampanga - Paguio, Ianna Glaiza S.; Pare, Charissa Francine A.
This study explored ginhawa, a Filipino indigenous concept of well-being, through the lives of folk healers, clients, and community residents from Pampanga. Rooted in pre-colonial culture and passed on from generation to generation, folk healing remains a living component of rural Filipino health care, particularly where modern medical facilities are inaccessible. Ginhawa, generally described as a condition of physical, emotional, spiritual, and social balance, is the core of the healing process and is pursued through culturally embedded practice forms like hilot, tawas, herbal medicine, and spiritual rituals. Through qualitative, holistic multiple-case study design, the researchers interviewed 15 participants through in-depth interviews to explore how ginhawa is conceptualized, embodied, and cultivated in folk healing. The thematic analysis demonstrated that ginhawa is not only a product of healing but also an organizing framework that informs care practice, inextricably linked to cultural values and spiritual beliefs. Findings emphasized the activities of folk healers as natural caregivers and custodians of culture, whose practice of healing provides a complementary perspective to modern psychological conceptualizations of well-being. This study highlighted the importance of acknowledging and promoting indigenous wellness models such as ginhawa in serving the psychosocial requirements of marginalized Filipino communities.